GLYCEROL TOXICITY AND QUALITY OF FROZEN-THAWED BALI CATTLE SPERMATOZOAS - S. A., LESTARI; ., DARMAWAN; ROSADI, B. (Majalah Ilmiah Peternakan, 2022)
This study aimed to determine the effect of glycerol concentration on motility, viability and abnormalities of frozen thawed spermatozoa of Bali cattle. The study was conducted using a completely randomized design with 5 treatments and 6 replications. The treatments consisted of T0 (0% glycerol), T1 (6% glycerol), T2 (12% glycerol), T3 (18% glycerol), P4 (24% glycerol). The results showed that the administration of glycerol had a very significant effect (p<0.01) on the motility, viability, and abnormality of spermatozoa. Six percent glycerol in diluent able to reduce the decrease in motility, viability. and prevent the increase of spermatozoa abnormality. Toxic effects of glycerol were higher in accordance to higher concentration started in 12%.